Efforts to Improve the English Test Reliability in SMP Negeri 1 Manisrenggo Klaten - Hidayatullah, Efendi (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2024)
This study aims to attempt to improve the reliability of English language tests. The qualitative research focused on the results of the English reliability test in the ninth grade of SMP Negeri 1 Manisrenggo Klaten. The study's results were analyzed and discussed in depth to find implications and contributions to efforts to improve the reliability of English tests, especially in grade nine. This study found reliability issues such as Student-Related Reliability, Rater Reliability, Test Administration Reliability, and Test Reliability Efforts to improve English test reliability at SMP N 1 Manisrenggo School, Klaten, can be enhanced by focusing on test content reliability. keyword:  Reliability, English language, test Penelitian ini bertujuan untuk Upaya meningkatkan reliability tes bahasa Inggris . Metode penelitian yang digunakan adalah qualitatif, dengan fokus pada hasil test bahasa Inggris pada kelas Sembilan SMP Negeri 1 Manisrenggo Klaten. Hasil penelitian dianalisis dan dibahas secara mendalam untuk menemukan implikasi dan kontribusi terhadap Upaya meningkatkan keandalan tes bahasa Inggris terutama pada kelas sembilan. Pada penelitian ini ditemukan masalah reability seperti  Reliabilitas Terkait Siswa, Reliabilitas Rater, Reliabilitas Administrasi Tes, dan Reliabilitas Tes Upaya untuk meningkatkan reliabilitas tes bahasa Inggris di Sekolah SMP N 1 Manisrenggo, Klaten, dapat ditingkatkan dengan memfokuskan pada reliabilitas isi tes. Kata kunci: Reliability, Bahasa Inggris, tes